2020
DOI: 10.1016/j.aanat.2020.151577
|View full text |Cite
|
Sign up to set email alerts
|

The practice of ethics in the context of human dissection: Setting standards for future physicians

Abstract: It is a much desirable skill among physicians that clinical practice should be guided by ethical norms. The dissection room experience provides an opportunity for nurturing the principles of ethical practice among medical students early in the curriculum. When the exercise of human dissection is followed within the boundaries of ethics it effectively props an ideal example for the young minds to emulate in the future. Hence in every stage of dissection room activity precious human body needs to be handled in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 67 publications
(110 reference statements)
0
53
0
4
Order By: Relevance
“…With regard to the journey of body donation in a medical school, it generally commences with the procurement of the donated body from a licensed source, followed by preservation of the body, then use in anatomical education and research, and eventually concludes with the respectful disposal of the remains of the donated body [ 69 ]. While the junctures of this journey differ, continuous and consistent adherence to ethical guidelines is paramount [ 69 ]. Moreover, Riederer et al.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the journey of body donation in a medical school, it generally commences with the procurement of the donated body from a licensed source, followed by preservation of the body, then use in anatomical education and research, and eventually concludes with the respectful disposal of the remains of the donated body [ 69 ]. While the junctures of this journey differ, continuous and consistent adherence to ethical guidelines is paramount [ 69 ]. Moreover, Riederer et al.…”
Section: Discussionmentioning
confidence: 99%
“…This will not only suffice in pandemics like Covid‐19 but also for the future. It is equally essential that ethical principles be followed, even when virtual dissections come into use (Ghosh, 2020). Care should be taken to ensure that cadavers are not being treated as mere teaching or research tools (Jones, 2017, 2020; Lalwani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several others believe that their use may have benefits beyond just teaching, including teaching about medical fallibility and uncertainty, as well as raising issues of death and dying [ 39 41 ]. As recently reviewed by Ghosh [ 42 ], the dissection room, along with the rules and steps for receiving, use, and disposal of cadaver materials gives crucial room to nurture the ethical practice principles among medical students early in the curriculum. Our present study adds evidence in support of the utility of cadavers beyond the learning of anatomical facts but building humanist doctors.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, feedback from students revealed that participation in ceremonies enhanced their commitment to studying, appreciating the value of dissection, personal growth, and strengthening of compassion. All these benefits of engagement in ceremonies have been reported in a variety of settings elsewhere [ 35 ] thereby placing anatomy at the core of early inculcation of humanist values in preclinical medical training [ 42 ]. Although most studies reported lacking a formal curriculum [ 27 , 46 ], the utility of such programs continues to appear frequently in recent literature [ 47 ].…”
Section: Discussionmentioning
confidence: 99%